Exploring the impact of health literacy on pregnant women from ethnic minority groups: A scoping review. - Sarah E Feldman; Laura Lennox; Natasha Dsouza; Keivan Armani (PLoS ONE)
Objective Health Inequalities refer to disparities in healthcare access and outcomes based on social determinants of health. These inequalities disproportionately affect Black, Asian, Minority Ethnic (BAME) groups, particularly pregnant women, who face increased risks and limited access to care due to low health literacy. Maternal mortality rates for BAME women can be up to four times higher than for white women. This scoping review aimed to assess the impact of health literacy on BAME pregnant women's health outcomes and experiences. Objectives included evaluating health literacy improvement tools, engaging stakeholders through co-production, and identifying persisting health inequalities. Data sources A scoping review using the Arksey and O'Malley's framework was conducted. A specific search strategy was developed with a research librarian across three databases: EMBASE, Medline, and the Maternity and Infant Care (MIC) database. Patient, Public Involvement, and Engagement (PPIE) members were consulted from the outset to co-design the research question and to provide feedback on the findings. Study appraisal and synthesis methods Out of 1958 articles, 19 were included in the study, with 47% from the US and 21% from Denmark. Articles were published from EMBASE. 47% of the articles measured health literacy, while 53% implemented health literacy interventions, such as digital or community-based approaches. Results All 19 articles highlighted lower health literacy in BAME women compared to other groups. Ten proposed recommendations, while others emphasized the impact of social determinants of health, collectively underscoring the need for more research on BAME health. Conclusions The review underscores the inadequate health literacy and patient experience of BAME pregnant women. It also highlights the potential of digital health interventions to improve health literacy and health outcomes. The findings call for increased research into health literacy tools for BAME pregnant women. Healthcare systems, including the NHS, should allocate resources to enhance digital health interventions and address health inequalities in BAME groups during pregnancy.